2017
DOI: 10.1007/s10482-017-0956-x
|View full text |Cite
|
Sign up to set email alerts
|

Roseomonas aeriglobus sp. nov., isolated from an air-conditioning system

Abstract: A novel pale pink-coloured, strictly aerobic, Gram-stain negative bacterial strain, designated strain KER25-12, was isolated from a laboratory air-conditioning system in South Korea. Cells were observed to be non-motile cocci showing positive catalase and oxidase reactions. Strain KER25-12 was found to grow at 10-30 °C (optimum, 25-30 °C), at pH 4.0-9.0 (optimum, pH 6.0-7.0) and in the presence of 0-2% (w/v) NaCl (optimum, 0%). Ubiquinone-10 and spermidine were detected as the sole respiratory quinone and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Basonym: Roseomonas aeriglobus (Lee and Jeon, 2018) The description of Pararoseomonas aeriglobus is the same as that of Roseomonas aeriglobus as given by Lee and Jeon (2018). The accession number for the 16S rRNA gene sequence is KY864922.…”
Section: Emended Description Of the Genusmentioning
confidence: 99%
“…Basonym: Roseomonas aeriglobus (Lee and Jeon, 2018) The description of Pararoseomonas aeriglobus is the same as that of Roseomonas aeriglobus as given by Lee and Jeon (2018). The accession number for the 16S rRNA gene sequence is KY864922.…”
Section: Emended Description Of the Genusmentioning
confidence: 99%
“…Members of this genus have a wide distribution in nature, and have primarily been isolated from clinical samples such as blood, wounds and genitourinary specimens [1][2][3][4][5]. They have also been isolated from different environmental samples, like Roseomonas aeriglobus [6], R. deserti [7], R. fluminis [8], R. globiformis [9] and R. radiodurans [10], which were separated from airconditioning systems, crude oil-contaminated desert sand, sediment of a shallow stream, urban area and gamma rayirradiated soil in the last 2 years. Bacteria in the genus Roseomonas have the following characteristics: Gram-stain-negative, aerobic, catalase-and oxidase-positive, and with Q-10 as the main menaquinone.…”
mentioning
confidence: 99%
“…The members of the genus Roseomonas are generally characterized as Gram-stain-negative, strictly aerobic and pink-pigmented. Members of the genus Roseomonas have been isolated from various environmental habitats, including water [2][3][4], cooling tower and water-cooling systems [5,6], air conditioners [7,8], soil [9][10][11], an oilcontaminated site [12], sediment [13][14][15] and clinical specimens [1,16]. Because it has been reported that some microbes living in algal spheres influence algal growth through some interactions, alga-associated bacteria have attracted a great deal of attention in order to understand algal growth [17].…”
mentioning
confidence: 99%